Biology and oncogenicity of the Kaposi sarcoma herpesvirus K1 protein - Sousa-Squiavinato, Annie Cristhine Moraes [UNESP]; Silvestre, Renata Nacasaki [UNESP]; Oliveira, Deilson Elgui de [UNESP] (Wiley-Blackwell, 2015)
The Kaposi sarcoma-associated herpesvirus (KSHV), or human herpesvirus 8, is a gammaherpesvirus etiologically linked to the development of Kaposi sarcoma, primary effusion lymphomas, and multicentric Castleman disease in humans. KSHV is unique among other human herpesviruses because of the elevated number of viral products that mimic human cellular proteins, such as a viral cyclin, a viral G protein-coupled receptor, anti-apoptotic proteins (e.g. v-bcl2 and v-FLIP), viral interferon regulatory factors, and CC chemokine viral homologues. Several KSHV products have oncogenic properties, including the transmembrane K1 glycoprotein. KSHV K1 is encoded in the viral ORFK1, which is the most variable portion of the viral genome, commonly used to discriminate among viral genotypes. The extracellular region of K1 has homology with the light chain of lambda immunoglobulin, and its cytoplasmic region contains an immunoreceptor tyrosine-based activation motif (ITAM). KSHV K1 ITAM activates several intracellular signaling pathways, notably PI3K/AKT. Consequently, K1 expression inhibits proapoptotic proteins and increases the life-span of KSHV-infected cells. Another remarkable effect of K1 activity is the production of inflammatory cytokines and proangiogenic factors, such as vascular endothelial growth factor. KSHV K1 immortalizes primary human endothelial cells and transforms rodent fibroblasts in vitro; moreover, K1 induces tumors in vivo in transgenic mice expressing this viral protein. This review aims to consolidate and discuss the current knowledge on this intriguing KSHV protein, focusing on activities of K1 that can contribute to the pathogenesis of KSHV-associated human cancers. Copyright © 2015 John Wiley & Sons, Ltd.